Fabricating porous ceramic materials via phase separations in blends of cellulose acetate and ceramic nanoparticles. Issue 8 (26th April 2022) - Hu, Hongli; Zhong, Hangyu; Zhang, Bo‐xing
Abstract: As applications of porous ceramic materials have gradually expanded, the novel technologies for the fabrication of porous ceramic materials with a delicate and controllable structure are still attractive. In this work, three types of porous monolithic ceramic materials, including Al2 O3 –SiO2, TiO2, and SiC, have been fabricated by thermally impacted and non‐solvent‐induced phase separations in blends of cellulose acetate and ceramic nanoparticles. These materials possessed three‐dimensional interconnected porous structures with low densities, high porosities, and hierarchical pores ranging from 5 nm to 6 μm. The relationships between microstructures and phase separations were systematically investigated. Furthermore, electromagnetic shielding effectiveness of 20 dB from 5 to 18 GHz in porous SiC materials has been achieved, revealing that those materials have potential applications in the electromagnetic shielding. This work provides a powerful and general approach to fabricate porous monolithic ceramic materials with a wide range of various ceramic nanoparticles. Abstract : Three types of porous monolithic ceramic materials, including Al2 O3 –SiO2, TiO2, and SiC, have been fabricated by thermally impacted and non‐solvent‐induced phase separations in blends of cellulose acetate and ceramic nanoparticles.